Green roofs influence on stormwater quantity and quality: a review - Santos, Cristina (2022)
This chapter intends to make an extensive review of the influence that Green Roofs (GR) have on the quality and quantity of stormwater. These aspects are very important to define the benefits and the disadvantages of this nature-based solution that is being implemented worldwide to improve the sustainability of urban areas. Previous studies show that the characteristics of GR (such as dimensions, the composition of the different layers and the type of plants) have a major influence on the quality and quantity of the GR runoff. Despite the proven benefits in urban stormwater management, in some reported cases, the quality resulted worst and for some GR conditions, the effect on rainwater retention was minimal. They are key elements to make resilient cities so a clear understanding of their functioning and development is fundamental to avoid and minimize potential impacts of malfunctioning of these nature-based structures.